JAM-C maintains VEGR2 expression to promote retinal pigment epithelium cell survival under oxidative stress - Jia, Xin; Zhao, Chen; Chen, Qishan; Du, Yuxiang; Huang, Lijuan; Ye, Zhimin; Ren, Xiangrong; Wang, Shasha; Lee, Chunsik; Tang, Zhongshu; Li, Xuri; Ju, Rong (Thrombosis and Haemostasis, 2017)
Junctional adhesion molecule-C (JAM-C) has been shown to play critical roles during development and in immune responses. However, its role in adult eyes under oxidative stress remains poorly understood. Here, we report that JAM-C is abundantly expressed in adult mouse retinae and choroids in vivo and in cultured retinal pigment epithelium (RPE) and photoreceptor cells in vitro. Importantly, both JAM-C expression and its membrane localisation are downregulated by H2O2-induced oxidative stress. Under H2O2-induced oxidative stress, JAM-C is critically required for the survival of human RPE cells. Indeed, loss of JAM-C by siRNA knockdown decreased RPE cell survival. Mechanistically, we show that JAM-C is required to maintain VEGFR2 expression in RPE cells, and VEGFR2 plays an important role in keeping the RPE cells viable since overexpression of VEGFR2 partially restored impaired RPE survival caused by JAM-C knockdown and increased RPE survival. We further show that JAM-C regulates VEGFR2 expression and, in turn, modulates p38 phosphorylation. Together, our data demonstrate that JAM-C plays an important role in maintaining VEGR2 expression to promote RPE cell survival under oxidative stress. Given the vital importance of RPE in the eye, approaches that can modulate JAM-C expression may have therapeutic values in treating diseases with impaired RPE survival.
Keywords: Junctional adhesion molecule-C; VEGR2; retinal pigment epithelium cell; cell survival